Advancing breast cancer circulating tumour cell research at the Institute of Oncology Ljubljana - Tanja Jesenko; Cvetka Grašič Kuhar; Živa Pišljar; Simona Miceska; Veronika Kloboves-Prevodnik; Maja Čemažar (Onkologija)
Circulating tumour cells (CTCs) have become an important biomarker in breast cancer, providing an insight into disease progression and monitoring of therapeutic response. Due to their extreme rarity in blood and the complexity of blood composition, their isolation and characterization is challenging. Specific isolation methods allow the enrichment of CTCs from a blood sample and facilitate further analysis. At the Institute of Oncology Ljubljana, in 2018 we initiated efforts to develop a simple method for the isolation and characterization of CTCs, aimed at identifying these cells through cytopathological analysis. We evaluated two different methods of CTC isolation in breast cancer patients based on different approaches. The first method is based on cell biological properties, such as the expression of the epithelial cell adhesion marker (EpCAM), while the second method is based on physical properties of CTCs, such as their larger size and deformability compared to other blood cells. We found that the physical method is more suitable, as it enables the isolation of higher numbers of morphologically intact CTCs. After isolation, cytological slides are prepared and then characterized by cytopathological analysis and immunocytochemical and immunofluorescence staining. This approach currently allows us to determine the number of single CTCs and CTC clusters in the blood, assess their morphological preservation, and identify their phenotype. In addition to evaluation of single CTCs and CTC clusters in ongoing clinical trials using currently established methods and the planned establishment of a translational platform in mouse models, we aim to expand the range of CTC studies in the future to include genomic and transcriptomic analysis.